2011
DOI: 10.3109/09513590.2010.534330
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of GDF-9, leptin, and IGF1 receptors associated with adipose tissue transplantation on fertility restoration in obese anovulatory mice

Abstract: The aim was to analyze the effect of adipose tissue transplantation on growth differentiation factor-9 (GDF-9), insulin growth factor 1 receptor (IGF1R), and leptin receptor (LEPR) protein expression in ovaries of obese anovulatory mice. Leptin-deficient female (ob/ob) and wild-type mice were divided into untreated ob/ob mice and gonadal white adipose tissue transplanted ob/ob mice, with evaluation after 7, 15, and 45 days and compared to control wild-type mice. The corporal weight and glycemia levels increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Sebastien Elis ,* † ‡ § 1 Stephanie Coyral-Castel ,* † ‡ § Sandrine Freret ,* † ‡ § Juliette Cognié ,* † ‡ § Alice Desmarchais ,* † ‡ § Alice Fatet ,* † ‡ § Christelle Rame ,* † ‡ § Eric Briant ,* † ‡ § Virginie Maillard ,* † ‡ § and Joëlle Dupont * † ‡ § Ali, 2010), as well as to exert some well-known effects on reproductive functions (Campos et al, 2008;Briana and Malamitsi-Puchner, 2010;Tersigni et al, 2011;Dupont et al, 2012). Moreover, some publications suggest a role of adipose tissue secretion in sustaining proper fertility; indeed, fat transplantation in leptin knockout mice restores fertility in these animals (Klebanov et al, 2005;Pereira et al, 2011). Leptin is suggested to be a link between energy balance and reproductive function (Diskin et al, 2003).…”
Section: Expression Of Adipokine and Lipid Metabolism Genes In Adiposmentioning
confidence: 99%
“…Sebastien Elis ,* † ‡ § 1 Stephanie Coyral-Castel ,* † ‡ § Sandrine Freret ,* † ‡ § Juliette Cognié ,* † ‡ § Alice Desmarchais ,* † ‡ § Alice Fatet ,* † ‡ § Christelle Rame ,* † ‡ § Eric Briant ,* † ‡ § Virginie Maillard ,* † ‡ § and Joëlle Dupont * † ‡ § Ali, 2010), as well as to exert some well-known effects on reproductive functions (Campos et al, 2008;Briana and Malamitsi-Puchner, 2010;Tersigni et al, 2011;Dupont et al, 2012). Moreover, some publications suggest a role of adipose tissue secretion in sustaining proper fertility; indeed, fat transplantation in leptin knockout mice restores fertility in these animals (Klebanov et al, 2005;Pereira et al, 2011). Leptin is suggested to be a link between energy balance and reproductive function (Diskin et al, 2003).…”
Section: Expression Of Adipokine and Lipid Metabolism Genes In Adiposmentioning
confidence: 99%
“…In Lep ob/ob mice, short-term leptin treatment may not correct hepatocyte dysfunction and steatosis (Leclercq et al 2006). Although WAT transplantation was effective for the treatment and prevention of obesity, as well as of endocrine/metabolic alterations associated with leptin deficiency, it exerted profound effects on multiple physiological functions in Lep ob/ob mice: reduced body weight gain and IR and restored fertility (Klebanov et al 2005, Sennello et al 2006, Barros et al 2009, Pereira et al 2011. However, the assessment of NAFLD progression after WAT transplantation has not been evaluated yet.…”
Section: Introductionmentioning
confidence: 99%
“…It is largely known that leptin plays a primary role in regulating homeostasis, obesity and fertility [23] [28]. Moreover, in a previous work, Pereira et al (2009) clearly demonstrated that WAT transplantation decreases insulin resistance and restores fertility in female ob/ob mice [9]. Behind these physiological and morphological changes lay complex molecular interactions that deserve to be better understood.…”
Section: Discussionmentioning
confidence: 99%
“…These animals were maintained in a temperature-controlled environment at approximately 24˚C under a 12/12-h light-dark cycle and were handled at least once a week. Five ob/ob mice received a white adipose tissue (WAT) transplant as described by Gavrilova and Marcus-Samuels et al (2000) [29] and Pereira et al (2011) [9]: the adipose gonad tissue samples that were obtained from the wild-type mice were placed in phosphate buffer solution (PBS) and fragmented into small pieces. The WAT grafts were implanted in the subcutaneous tissue through small, shaved skin incisions on the dorsal region of the animal, which was anesthetized with isoflurane.…”
Section: Experimental Animals and Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation